2000
DOI: 10.1159/000012380
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dimensions of Alexithymia and Dissociation

Abstract: Background: The study investigated the following hypotheses: (1) Alexithymia is significantly associated with dissociation. (2) Pathological versus nonpathological dissociation is associated with alexithymic traits. Methods: Psychiatric in- and outpatients (n = 173) and nonclinical subjects (n = 38) were investigated with the Toronto Alexithymia Scale (TAS-20), the FDS (German version of Dissociation Experience Scale) and the Symptom Check List (SCL-90-R; GSI). Correlation analyses followed by MANOVA and logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 26 publications
(40 reference statements)
11
61
0
2
Order By: Relevance
“…It is associated with reluctance to express emotion, a lack of fantasy or imagination, and a tendency to think and problem-solve in concrete terms (Taylor et al, 1990). The TAS is positively correlated with neuroticism/negative emotionality, negatively correlated with extraversion/positive emotionality (Parker, Taylor, & Bagby, 1989), and it has been linked to a range of psychopathological processes and syndromes including PTSD severity (Monson, Price, Rodriguez, Ripley, & Warner, 2004), other anxiety disorders, hypochondria, eating disorders (Taylor & Bagby, 2000), and dissociation (Grabe, Rainermann, Spitzer, Gansicke, & Freyberger, 2000). Alpha for the current sample was .80.…”
Section: Pennebaker Inventory Of Limbic Languidness (Pill;pennebakermentioning
confidence: 73%
“…It is associated with reluctance to express emotion, a lack of fantasy or imagination, and a tendency to think and problem-solve in concrete terms (Taylor et al, 1990). The TAS is positively correlated with neuroticism/negative emotionality, negatively correlated with extraversion/positive emotionality (Parker, Taylor, & Bagby, 1989), and it has been linked to a range of psychopathological processes and syndromes including PTSD severity (Monson, Price, Rodriguez, Ripley, & Warner, 2004), other anxiety disorders, hypochondria, eating disorders (Taylor & Bagby, 2000), and dissociation (Grabe, Rainermann, Spitzer, Gansicke, & Freyberger, 2000). Alpha for the current sample was .80.…”
Section: Pennebaker Inventory Of Limbic Languidness (Pill;pennebakermentioning
confidence: 73%
“…The construct of alexithymia focuses on difficulties in describing and expressing feelings, on the paucity of fantasies. Recent studies have associated alexithymia with dissociation [3], depression [4,5,6], anxiety disorders [7, 8], pathological gambling [9] and a broad range of psychopathologic features [10]. Given the relative temporal stability [11,12,13,14,15,16], the pattern of correlations with traits of personality models like the NEO-FFI and the temperament and character model [17,18,19], alexithymia is considered to be a unique and distinct personality construct.…”
Section: Introductionmentioning
confidence: 99%
“…Following the same line of research Mason et al (2005) came up with a relationship between 'difficulty identifying feelings' and two subscales of dissociation on the DES, namely 'Depersonalization' and 'Absorption'. Another study comparing clinical and non-clinical subjects also came up with a strong positive correlation between alexithymia and dissociative symptomatology (Grabe et al, 2000). However, even though alexithymia and dissociation share features (for instance in the domain of fantasy) convincing evidence has been brought forward for two distinct constructs (Lipsanen et al, 2004).…”
Section: )mentioning
confidence: 99%
“…Other commonly documented disturbances, also related to CSA, are depression, anxiety, eating disorders and self-mutilation (Parker, Bagby & Taylor, 1991;Zlotnick et al, 1996;Lipsanen et al, 2004). One common ground between the two phenomena is a displayed inability of the patients to consciously integrate segments of neuropsychological functions such as memories and feelings (Grabe et al, 2000). Elzinga et al (2002) reported that dissociative tendencies where related to a general 'difficulty in identifying one's own feelings' as part of a response to periods of stress.…”
Section: )mentioning
confidence: 99%